1965
DOI: 10.1139/b65-154
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Corynespora Cassiicola on Soybean

Abstract: Corynespora cassiicola was pathogenic on the roots and hypocotyls of soybean seedlings grown in infested soil at Ottawa. Extensive superficial necrotic lesions developed on seedlings from inoculated seeds planted in the field in mid-May, but few symptoms appeared on seedlings planted in late May and in June. Infected plants were initially stunted but recovered with little effect on size or yield. In controlled temperature studies, severe root and hypocotyl rot were produced on inoculated seedlings at 15–20 °C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 1 publication
1
19
0
2
Order By: Relevance
“…Fusarium oxysporum and F. solani were reported as pathogens causing Fusarium wilt, Fusarium blight and root rot of soybeans in Korea [17]. Phomopsis longicolla and Corynespora cassiicola were reported as pathogenic fungi to soybeans in other countries [18, 19]. Additionally, B. dothidea , F. fujikuroi , Khuskia oryzae , and P. oxalicum , were reported as pathogenic fungi in other plants [17].…”
Section: Resultsmentioning
confidence: 99%
“…Fusarium oxysporum and F. solani were reported as pathogens causing Fusarium wilt, Fusarium blight and root rot of soybeans in Korea [17]. Phomopsis longicolla and Corynespora cassiicola were reported as pathogenic fungi to soybeans in other countries [18, 19]. Additionally, B. dothidea , F. fujikuroi , Khuskia oryzae , and P. oxalicum , were reported as pathogenic fungi in other plants [17].…”
Section: Resultsmentioning
confidence: 99%
“…usually causes target spot on leaves but also on stems, roots and flowers of more than 280 host plants from over 70 tropical and subtropical countries (Farr et al 2007). The organism has been reported on a great number of economically important crops including tobacco (Fajola and Alasoadura 1973), cowpea (Olive et al 1945), eggplant (Onesirosan et al 1974), sesame (Stone and Jones 1960), tomato (Mohanty and Mohanty 1955), soybean (Seaman and Shoermaker 1964), cucumber (Blazquez 1967), cotton (Jones 1961) and Hevea rubber (Deighton 1936). The Corynespora Leaf Fall (CLF) disease caused by the fungus C. cassiicola was first identified on Hevea rubber (Hevea brasiliensis) in Sierra Leone in 1936 (Deighton 1936).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of corynespora rot may be attributable to the late seeding (June 14). Seaman et al (1965) found that early plantings of infected seedlings (mid-May) favored corynespora rot, whereas later plantings in June resulted in a negligible amount of root rot. Moreover, the presence of this fungus may account for the poor germination of the flrst seeding (Mack and Ivarson 1972).…”
Section: Resultsmentioning
confidence: 96%